Lithuanian bibliographic production in 1986-2000 (quantitative analysis) - Janonis, Osvaldas (Knygotyra, 2003)
The subject of analysis in the article is bibliographic aids published in Lithuania in 1986–2000. The author establishes some trends in the adaptation of the system of bibliographic publications to the new political and economic conditions, like: orientation to the changing information needs of users, new topics of bibliographic coverage, diminishing print runs, increasing numbers of personal bibliographic aids, disappearance of popular (recommendatory) bibliography, etc.